QUALITY RISK MANAGEMENT FOR SALBUTAMOL PRESSURIZED METERED DOSE INHALERS - N. A. Lyapunov; E. P. Bezuglaya; V. A. Bovtenko; Yu. M. Stolper; V. N. Baumer; E. Yu. Bryleva (Разработка и регистрация лекарственных средств, 2019)
The risks for the functional characteristics of Salbutamol pressurized metered dose inhaler (pMDI), such as the uniformity of delivered dose, the distribution of salbutamol particles at the stages of the Andersen impactor (apparatus D), and the respirable fraction, were studied and identified. It is shown that these risks can be associated with the solubility of salbutamol sulfate (SS), the formulation of pMDI, the water content in the SS and ethanol, as well as the particle size distribution of SS. A relationship is shown between the particle size distribution of the SS, the rate of their sedimentation and the performance characteristics of the preparation. The properties of SS crystals are investigated and the possibility of enantiomers presence is shown. The risks associated with the production process, the materials of the primary packaging and the correctness of the quality control procedures are discussed. It is shown that the use of containers made of aluminum alloy EN AW-5052-0 without internal coating does not pose the risk of the release of elemental impurities into the preparation. Unjustified replacement of actuators may pose a risk to the performance characteristics of Salbutamol pMDI and in vitro equivalence as compared with the reference medicinal product.